1981
DOI: 10.1113/jphysiol.1981.sp013716
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetically induced changes in the responses of guard hair and type II receptors in the cat.

Abstract: SUMMARY1. Sympathetic effects on the activity of single guard hair receptors and slowly adapting, type II mechanoreceptors were studied in anaesthetized cats.2. Spontaneous activity in type II receptors and mechanically evoked activity in both type II and guard hair receptors was recorded both without and with electrical stimulation of the lumbar sympathetic trunk.3. Almost all guard hair receptors were desensitized by sympathetic stimulation, the mean effect being an increase in threshold to 2-2 times the unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…In the light of the present results the question of whether the sympathetic inhibition could be due to indirect effects on blood flow or skin compliance must be considered. Depression of responses of guard and down hair units by sympathetic stimulation has also been described in the rabbit ear (Barasi and Lynn 1986) and the cat hind limb (Pierce and Roberts 1981). These studies concluded that sympathetic effects were unlikely to be due to indirect changes in blood flow.…”
Section: Discussionmentioning
confidence: 51%
“…In the light of the present results the question of whether the sympathetic inhibition could be due to indirect effects on blood flow or skin compliance must be considered. Depression of responses of guard and down hair units by sympathetic stimulation has also been described in the rabbit ear (Barasi and Lynn 1986) and the cat hind limb (Pierce and Roberts 1981). These studies concluded that sympathetic effects were unlikely to be due to indirect changes in blood flow.…”
Section: Discussionmentioning
confidence: 51%
“…There may be other classes of postganglionic sympathetic neurone supplying skin that have yet to be characterized. For example, there is evidence that activity in sympathetic fibres can cause modulation of the sensitivity of cutaneous receptors by a mechanism other than altering the local blood flow (Pierce & Roberts, 1981;Roberts, Elardo & King, 1985;Barasi & Lynn, 1986; but also note Shea & Perl, 1985c): the physiological significance of these effects is a matter of some doubt (for fuller discussions see Janig, 1985bJanig, , 1989.…”
Section: Cutaneous Nervesmentioning
confidence: 99%
“…In general all the experiments using amphibian or in vitro mammalian preparations have reported purely excitatory responses to sympathetic stimulation or superfused noradrenaline (Loewenstein, 1956;Loewenstein & Altamirano-Orrego, 1956;Chernetski, 1964;Spray, 1974; Schiff, 1974;Calof, Jones & Roberts, 1981). In contrast, those using in vivo mammalian preparations have reported either mixed responses (Hunt, 1960;Eldred, Schnitzlein & Buchwald, 1960;Edwall & Scott, 197 1 ;Freeman & Rowe, 1981;Pierce & Roberts, 1981;Roberts & Levitt, 1982;Barasi & Lynn, 1983), or suppressive responses (Nilsson, 1972;Cash & Linden, 1982;Barasi & Lynn, 1983;Passatori & Filippi, 1983).…”
Section: Introductionmentioning
confidence: 99%